Profile of Medicolegal Autopsies at a Provincial Hospital in Nepal - Gurung , Sharmila; Shrestha, Ahana; Shrestha, Sugam (Medical Journal of Eastern Nepal, 2025)
Background: Autopsies provide crucial insight into the lives of the deceased. Recording and reporting their findings contribute to the health information management system, which helps to develop or reform health policies or priorities. We aim to study the frequency of deceased by age and sex, determine if there is a sex difference as well as age in the autopsies, and its relation to the manner of death. Methods: This cross-sectional observational study was conducted on the medicolegal autopsies from Lumbini Provincial Hospital within a one-year duration. The data was collected from the mortuary register and entered into Microsoft Excel and analysed. Statistical analyses included a Chi-square test. Results: 469 cases were autopsied, of which males and females comprised 75% and 25%, respectively. Adults (67%) were the highest among the deceased. Statistical difference was observed between age and sex, similarly, between manner and sex, but not with manner and age. Most deaths were unnatural (83%), followed by natural (6%), and in 53 (11%), the manner could not be determined. Maximum deaths were due to road traffic accidents (43%) and accidents (28.3%), being the most common manner of death. Conclusion: Young adult males died from road traffic accidents. There was a difference in the proportion of the gender and grouped age. The deceased’s gender varied with age and manner of death.